Case report: Giant coronary artery aneurysms with severe stenosis and multiple abdominal artery aneurysms - Gao, Hongli; Li, Hongwei (Frontiers in Medicine, 2023)
Background: Giant coronary artery aneurysms (GCAAs) were relatively rare. Little was known about its characteristics, its etiology and its therapy. GCAAs with multiple abdominal artery aneurysms (AAAs) were more unusual and rarer. Case presentation: A 29-year-old female presented to our hospital with abrupt-onset abdominal pain in the left upper quadrant and then she died in 2018. In 2016, prior to this visit, she came to our department for intermittent retrosternal compression pain during rest or sports activities. Medical history showed she had a coronary artery aneurysm (CAA) in 2004. We found evidence of multiple coronary aneurysms with severe stenosis and multiple AAAs and coronary artery bypass grafting (CABG) was carried out. In combination with laboratory analysis, imaging studies, and pathological examination, CAA may result from the long-term effects of Kawasaki disease (KD). Finally, the patient died of a ruptured abdominal aneurysm. Conclusions: We report a rare case of GCAAs with severe stenosis and multiple AAAs in a young woman with a history of KD-induced coronary aneurysm. Although the understanding of the optimal treatment strategy for GCAAs combined with multiple aneurysms was limited, we found that CABG was effective in the treatment of GCAAs in this patient. In the clinical treatment of patients with GCAAs, attention should be paid to the examination of systemic blood vessels.